Rheological properties of porcine organs: measurements and fractional viscoelastic model - Mishra, Aadarsh; Cleveland, Robin O. (Frontiers in Bioengineering and Biotechnology, 2024)
The rheological properties of porcine heart, kidney, liver and brain were measured using dynamic oscillatory shear tests over a range of frequencies and shear strains. Frequency sweep tests were performed from 0.1 Hz to a maximum of 9.5 Hz at a shear strain of 0.1%, and strain sweep tests were carried out from 0.01% to 10% at 1 Hz. The effect of pre-compression of samples up to 10% axial strain was considered. The experimental measurements were fit to a Semi-Fractional Kelvin Voight (S-FKV) model. The model was then used to predict the stress relaxation in response to a step strain of 0.1%. The prediction was compared to experimental relaxation data for the porcine organ samples, and the results agreed to within 30%. In conclusion, this study measured the rheological properties of porcine organs and used a fractional viscoelastic model to describe the response in frequency and time domain.